Seawater stable isotopes from the southeastern Atlantic during the GO-SHIP A13.5 2024 expedition - Weinhart, Alexander Helmut; Haumann, Alexander; Robertson, Emma; Meyer, Hanno; Marent, Andreas; Weiner, Mikaela (PANGAEA, 2025)
Seawater stable isotopes, namely hydrogen and oxygen isotopic composition, were measured from samples taken along the transect A13.5 in the southeastern Atlantic Ocean on the R/V Marcus G. Langseth in support of the Global Ocean Ship-based Hydrographic Investigation Program (GO-SHIP). This program occupies a set of hydrographic transects, such as A13.5, at approximately decadal resolution with full water column measurements to study physical, hydrographic, and chemical changes over time. In the period between February 1, 2024 and March 23 2024, 112 stations were accomplished during this cruise (with isotope samples at 75 stations), with latitudes between 1°20'N and 54°S and longitudes between 3°W and 2°E. Throughout the transect, a total of 268 samples were taken from the Niskin bottles in 30 ml plastic bottles with a screw cap (rinsed twice) from a range of depth levels for the measurement of seawater stable isotopes. The samples were shipped to the laboratory with intermittent storage until June 5, 2024. During transit and storage the samples were permanently cooled at about 4°C and not frozen. Samples were measured in the AWI ISOLAB Facility - Stable Isotope Laboratory Potsdam (see hdl:10013/sensor.ddc92f54-4c63-492d-81c7-696260694001) in the period from June to October 2024 and quality checked at AWI. The samples were measured using common equilibration technique with a Finnigan MAT Delta-S mass spectrometer (see hdl:10013/sensor.af148dea-fe65-4c87-9744-50dc4c81f7c9) equipped with two equilibration units for the online determination of the hydrogen and oxygen isotopic composition. This dataset provides the corresponding measurements (reported as permille deviation of the oxygen-18 to oxygen-16 ratio (DEL18O) and hydrogen to deuterium ratio (DELD), results are based on a 2-point calibration of two internal standards), error estimates (based on the standard deviation of repeat measurements), and quality flags along the transect. The corresponding CTD and bottle file is published at CCHDO.
Keywords: A13.5; Atlantic; d18O; dD; GO-SHIP; isotopes